An outlook on the energy mix at South African beverage manufacturers and opportunities for greater adoption of renewable energy solutions - Rozon, François Joseph André (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.